Expression profiling in neuroscience - Karamanos, Yannis (Humana Press, 2012)
DNA Microarrays for Gene Expression Analysis in Brain Tissue and Cell Lines -- Gene Expression Profiling Using the Terminal Continuation (TC) RNA Amplification Method for Small Input Samples in Neuroscience -- Expression Profiling In Brain Disorders -- Endothelial Cell Heterogeneity of Blood-Brain Barrier Gene Expression: Analysis by LCM/qRT-PCR -- Gene Expression Profiling Using 3' Digital Tag Approach -- Sharing Expression Profiling Data with Gemma -- Two-Dimensional Protein Analysis of Neural Stem Cells -- iTRAQ Proteomics Profiling of Regulatory Proteins During Oligodendrocyte Differentiation -- Protein Profiling of the Brain: Proteomics of Isolated Tissues and Cells -- The Proteome of Brain Capillary Endothelial Cells: Towards a Molecular Characterization of an In Vitro Blood-Brain Barrier Model -- MALDI Imaging Technology Application in Neurosciences: From History to Perspectives -- Profiling of HIV Proteins in Cerebrospinal Fluid -- Proteomic Profiling of Cerebrospinal Fluid -- New Nanotechnology Applications in Single Cell Analysis: Why and How.
Keywords: Neurowissenschaften; Genexpression